2009
DOI: 10.1111/j.1365-2672.2008.04096.x
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR detection and quantification of fish probioticPhaeobacterstrain 27-4 and fish pathogenicVibrioin microalgae, rotifer,Artemiaand first feeding turbot (Psetta maxima) larvae

Abstract: Aims:  To develop a SYBR Green quantitative real‐time PCR protocol enabling detection and quantification of a fish probiotic and two turbot pathogenic Vibrio spp. in microcosms. Methods and Results:  Phaeobacter 27‐4, Vibrio anguillarum 90‐11‐287 and Vibrio splendidus DMC‐1 were quantified as pure and mixed cultures and in presence of microalgae (Isochrysis galbana), rotifers (Brachionus plicatilis), Artemia nauplii or turbot (Psetta maxima) larvae by real‐time PCR based on primers directed at genetic loci cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…Previous reports also indicate that both the detection frequency and number of cells detected in feces by qPCR are substantially higher than the corresponding values obtained using culture methods. 26,48,49) The results of Fujimoto et al 35) were similar to ours in that the number of ingested bacteria detected by qPCR was tens of times higher than the number detected using the culture method. Essentially all bacteria with intact chromosomal DNA can be detected using the PCR method, whether they are alive or dead.…”
Section: ±08 Per Gramsupporting
confidence: 75%
“…Previous reports also indicate that both the detection frequency and number of cells detected in feces by qPCR are substantially higher than the corresponding values obtained using culture methods. 26,48,49) The results of Fujimoto et al 35) were similar to ours in that the number of ingested bacteria detected by qPCR was tens of times higher than the number detected using the culture method. Essentially all bacteria with intact chromosomal DNA can be detected using the PCR method, whether they are alive or dead.…”
Section: ±08 Per Gramsupporting
confidence: 75%
“…This supports the proposal that one way of utilizing Phaeobacter spp. in aquaculture is by introducing them directly into the live feed systems (Planas et al ., 2006; Prol et al ., 2009; Grotkjær et al ., 2016b). …”
Section: Discussionmentioning
confidence: 99%
“…The natural microbiome may harbour bacteria resistant to the antibiotic marker, the antibiotic marker may be unstable, and the marker may affect the fitness of the tagged strain, all of which can result in over‐ or underestimation of the actual abundances (Andersson and Levin, 1999; Allen et al ., 2010). Several non‐growth dependent methods have been developed for detection and/or quantification of vibrios (Eiler and Bertilsson, 2006; Prol et al ., 2009; Saulnier et al ., 2009; Kim and Lee, 2014). However, as previously described, vibrios are part of the established microbiota of live feed, thus genus‐ or species‐specific primers will potentially amplify vibrios from the background microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, real time-PCR and PCR-DGGE have been utilised to assess biotic bioencapsulation. Prol et al [146] development and validated a real time-PCR protocol for quantification of Phaeobacter 27-4 (previously described as Roseobacter 27-4) into live feeds and turbot larvae. The study demonstrated that bioencapsulation resulted in Phaeobacter 27-4 constituting 12% of the culturable bacteria in rotifers.…”
Section: Live Food Applicationsmentioning
confidence: 99%
“…Non-probiotic Vibrio spp.Best observation of fluorescently stained cells in the digestive tract of Artemia and shrimp mysis ranged between 15 min and 48 h. Prol et al[146] Development and validation of real time-PCR protocols for quantification of Phaeobacter 27-4* and Vibrio pathogens in live feeds and turbot larvaePhaeobacter 27-4* Phaeobacter27-4* could be accurately quantified by real time-PCR but estimated Vibrio levels in some samples were lower than plate counts. Phaeobacter 27-4* did not affect rotifer survival or growth.…”
mentioning
confidence: 98%